Potential for nutrient contribution from litter in a seasonally dry forest - José Fredson Bezerra Lopes; Eunice Maia Andrade; Lindbergue Araújo Crisóstomo; Meilla Marielle Araújo Rodrigues (Agro@mbiente On-line)
Litter is the most important way of transferring essential elements from vegetation to the soil. This is due to nutrient cycling, a process by which decomposition of the litter adds nutrients to the soil. An understanding of this process goes beyond the need for knowledge of nutrient dynamics, since it is a question of understanding the way in which ecosystems function in the search for a correct use of natural resources. The aim of this study was to quantify the average concentrations of the following nutrients: Nitrogen (N), phosphorus (P), Potassium (K), and Organic Carbon (C) in litter remaining in an area of tropical dry forest - Caatinga. The work was carried out on the Elias Andrade Private Natural Heritage Reserve (PNHR) of the Irmãos Andrade Farm, located in the semi-arid region of the State of Ceará. In February 2009, 48 nylon litter bags were randomly distributed, each containing 30 g of litter collected in the area of the Reserve. Every two months, from February 2009 to January 2011, four bags were randomly collected. Over time, variations were seen in the average levels of N, P and K for the litter in the nylon bags. The nutrient with the greatest contribution to the system from the litter was Nitrogen, followed by K and P. The highest N content occurred at the beginning of the experiment. The C content decreased over the study period. The mean C to N ratio of the litter was 21, which was in the borderline range between the processes of mineralisation and immobilisation.